2013
DOI: 10.2478/plc-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Pilot assessment of nonverbal pragmatic ability in people with asperger syndrome

Abstract: The purpose of this study is to present a diagnostic tool to assess the nonverbal pragmatic behaviors of people with Asperger syndrome, with the intent to give an account of the severity of symptoms in the area of nonverbal interaction, as well as providing a profile of nonverbal behaviors that may be targeted for intervention. Through this communication profile, overall nonverbal ability is calculated in a group of 20 subjects with Asperger syndrome. The proposed scale also includes the measurement of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Posters with ASD experienced (a) positive, (b) negative, and (c) hybrid FTAs. Like past research, those with ASD reported that their communication differences violated neurotypical norms (Caldwell-Harris & Jordan, 2014;Paul et al, 2008;Rodríguez Muñoz, 2013), that they experienced stigma (Bachmann et al, 2019), and social isolation (Gillespie-Lynch et al, 2014). In response to the FTAs, posters mitigated their face-loss using (a) preventive, (b) corrective, and (c) future facework.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Posters with ASD experienced (a) positive, (b) negative, and (c) hybrid FTAs. Like past research, those with ASD reported that their communication differences violated neurotypical norms (Caldwell-Harris & Jordan, 2014;Paul et al, 2008;Rodríguez Muñoz, 2013), that they experienced stigma (Bachmann et al, 2019), and social isolation (Gillespie-Lynch et al, 2014). In response to the FTAs, posters mitigated their face-loss using (a) preventive, (b) corrective, and (c) future facework.…”
Section: Discussionmentioning
confidence: 63%
“…For example, during conversations, individuals with ASD often provide irrelevant details, shift the topic at inappropriate times, are unresponsive to partner cues, fail to engage in reciprocal exchange, use unusual intonation, are formal, and are often preoccupied (Paul et al, 2008). Further, individuals with ASD might fail to make eye contact, adjust their facial expressions to what they are saying, maintain a rigid/tense posture, and fail to naturally produce gestures during conversations (Rodríguez Muñoz, 2013). Additionally, individuals with ASD might have a special interest or hobby they focus on and are particularly interested in, like history (Caldwell-Harris & Jordan, 2014).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of clinical linguistics, the study of pauses in spontaneous speech has a long tradition and has dealt with different pathologies (Beltrame et al 2011;Feenaughty et al 2013;Nordness et al 2010;Rosen et al 2010;Spitzer et al 1994;Tapia-Ladino 2003;Tjaden and Wilding 2011;Wingate 1984). It is well-known that high-functioning autism spectrum disorder (HFASD) is characterized, among other aspects, by prosodic alterations (Diehl and Paul 2013;Heikkinen et al 2010;Niemi 2008;Rodríguez-Muñoz 2009a, 2013aShriberg et al 2001;Thurber and Tager-Flusberg 1993). These irregularities have been associated with rhythm, tempo, intonation and/or volume (Baltaxe 1981;Gillberg and Gillberg 1989), but extend to DOI: 10.1075/prag.25.2.05rod 230 Francisco J. Rodríguez-Muñoz other nonverbal components such as eye gaze, facial expression, gestures, proxemics, body language or posture (Rodríguez-Muñoz 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite showing an appropriate management of grammatical rules, AS has been explained by diverse atypical verbal and non-verbal communicative behaviours. These particularities include pedantic or sophisticated vocabulary, prosodic and kinetic alterations, and other conversational particularities associated with turn-taking agility or conversational participation, among others (Rodríguez Muñoz, 2012;2013b;2017).…”
Section: Introductionmentioning
confidence: 99%